2009
DOI: 10.7880/abas.8.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Japanese Industrial Districts Combining Supplier-Side and Purchaser-Side Logic

Abstract: This paper proposes to combine supplier-side and purchaser-side logic in a new model of Japanese industrial districts. We interviewed large retail firms that were purchasers for industrial districts and 21 small-scale firms located in Tokyo's Ota Ward and Joto area that were the suppliers. Our interviews clearly highlighted the importance of business practices called "Kouza" and "Chouai." Large enterprises on the purchaser side deal only with kouza-holding firms (direct suppliers) and chouai-saki, which coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…For example, it includes people who capture demand from the market outside the industrial agglomeration and arrange the production network within it. They can exploit the strength of the industrial agglomeration (Inamizu & Wakabayashi, 2009, 2013.…”
Section: Theories Of Transfirm Organizationsmentioning
confidence: 99%
“…For example, it includes people who capture demand from the market outside the industrial agglomeration and arrange the production network within it. They can exploit the strength of the industrial agglomeration (Inamizu & Wakabayashi, 2009, 2013.…”
Section: Theories Of Transfirm Organizationsmentioning
confidence: 99%
“…Allen and Cohen (1969) and Allen (1977) are known for identifying the existence and effectiveness of the "gatekeeper" in research and development organizations. Even recently in Japan, this concept inspires a lot of research, for example, Harada (1999), Kuwashima, Takahashi, and Tamada (2005), Inamizu and Wakabayashi (2009).…”
Section: Allen's Research Projectsmentioning
confidence: 99%
“…Studies have identified the importance of company networks in an industry (Konno, 2003) and regions (Inamizu & Wakabayashi, 2009) in Japan; however, it is difficult to apply companies' concept of economies of size to the growth of the networks. However, it is possible to apply the concept of economies of growth to the growth of the networks, and such a case already exists.…”
Section: Concluding Hypothesismentioning
confidence: 99%